Interlimb Coordination Performance in Seated Position in Persons With Multiple Sclerosis: Reduced Amplitude Over 6 min and Higher Coordination Variability in Persons With Walking Fatigability - Goetschalckx, Mieke; Van Geel, Fanny; Meesen, Raf; Triccas, Lisa Tedesco; Geraerts, Marc; Moumdjian, Lousin; Feys, Peter (Frontiers in Human Neuroscience, 2021)
Background: Walking fatigability is prevalent in MS and can be measured by a percentage distance decline during a six-minute walking test. Walking is characterized by an accurate and consistent interlimb antiphase coordination pattern. A decline in coordination each minute during a six-minute walking test is observed in persons with MS (pwMS). Measuring coordination during a six-minutes seated coordination task with minimized balance and strength requirements, is assumed to examine a more fundamental interlimb antiphase coordination pattern in pwMS. This research aimed to answer the following research question: How does interlimb antiphase coordination pattern change during a seated coordination task in pwMS with walking fatigability (WF), non-walking fatigability (NWF) and Healthy Controls (HC)? Methods: Thirty-five pwMS and 13 HC participated. Interlimb coordination was assessed by a seated six-minutes coordination task (6MCT) with the instruction to perform antiphase lower leg movements as fast as possible. Outcomes were Phase Coordination Index (PCI) and movement parameters (amplitude, frequency). Results: Mixed models revealed a significant effect of time for the the variability of generating interlimb movements, with a difference in mean values between WF and HC. A significant group*time interaction effect was found for movement amplitude, represented by a significant decrease in movement amplitude in the WF group from minute 1 to the end of the task. Conclusion: The higher variability in interlimb coordination and decrease in movement amplitude over time during the 6MCT in the WF group could be an indicator of decreased control of fundamental antiphase coordination pattern in pwMS with walking fatigability. Trial Registration: www.clinicaltrials.gov NCT04142853 (registration date: October 29, 2019) and NCT03938558 (registration date: May 6, 2019)